SOSIALISASI REGULASI SISTEM NAVIGASI DAN MONITORING PERMESINAN KAPAL PENGRAJIN KAPAL KAYU PINISI DI TANABERU KABUPATEN BULUKUMBA - Rahimuddin; Lukmanul Hakim Arma; Erwin Eka Putra; Awalia Sulastri; Malika Amil Madani; Muhammad Assiddiq; Wulan Purnamasari; Masyhuri Damis (LP2M Universitas Hasanuddin, 2023)
Pinisi wooden ships were originally used to transport goods between islands. With the development of sea tourism, the design of the Pinisi has gradually changed into a modern tourist ship. The ships are built at the shipyard in Bulukumba. Some shipowners have upgraded the navigational equipment and installed the digitally controlled machinery at shipyards in Java. The use of these devices is regulated by the Ministry of Transport, which the owners and the craftsmen have to understand. Efforts to increase the knowledge of craftsmen and ship owners about digital-based navigation and monitoring equipment are being carried out through outreach activities with materials, including government regulations and electronic digital devices. Props were made to help explain the material. At the end of the activity, evaluation was carried out by comparing the answers to the questions asked at the beginning and the end of the training. The evaluation results showed that most of the participants understood the applicable regulations and the digital technology taught. Achievement of the activity: 68% of participants understood the material presented. — Kapal kayu Pinisi pada awalnya digunakan untuk mengangkut barang antar pulau. Dengan berkembangnya wisata laut, desain Pinisi berangsur-angsur berubah menjadi kapal wisata modern. Kapal-kapal ini dibangun di Bulukumba. Beberapa pemilik kapal telah meng-upgrade peralatan navigasi dan memasang mesin yang dikontrol secara digital di galangan kapal di Jawa. Penggunaan perangkat ini diatur oleh kementerian Perhubungan yang harus dipahami oleh pemilik dan nahkoda kapal. Upaya untuk meningkatkan pengetahuan para perajin dan pemilik kapal tentang peralatan navigasi dan pemantauan berbasis digital dilakukan melalui kegiatan sosialisasi dengan materi yang mencakup peraturan pemerintah dan perangkat digital elektronik. Alat peraga dibuat untuk membantu menjelaskan materi tersebut. Pada akhir kegiatan, dilakukan evaluasi dengan membandingkan jawaban dari pertanyaan yang diajukan di awal dan di akhir kegiatan. Hasil evaluasi menunjukkan bahwa sebagian besar peserta memahami peraturan yang berlaku dan teknologi digital.